A Giant Splenic Hydatid Cyst. Issue 1 (1st January 2016) - Singal, Rikki; Sandhu, Karamjot Singh; Mittal, Amit; Gupta, Samita; Jindal, Gunjan
Abstract : A 16-year-old girl presented with pain in the left hypochondrium, which had been progressing for 5 months. Examination revealed large splenomegaly, and ultrasonography showed a huge hydatid cyst in the spleen. Preoperative planning and postoperative care lead to successful management of this entity. Radiological investigations also play a major role in diagnosis and decrease morbidity.